2010
DOI: 10.1007/s00198-010-1494-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and costs of osteoporotic patients with subsequent non-vertebral fractures in the US

Abstract: NV fracture patients are at substantial risk for subsequent NV fractures within 1 year, and patients who incur subsequent fractures are significantly more costly than those who do not during the year following an incident fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
1
25
1
2
Order By: Relevance
“…The treatment costs borne by the patients with the second fracture were significantly higher compared with single fracture patient, which is consistent with previous studies in USA and UK [ 16 18 ]. In this study, those with the second vertebral fracture bore more than twice of total medical costs and fracture treatment costs when comparing their point estimates with those with a single vertebral fracture.…”
Section: Discussionsupporting
confidence: 91%
“…The treatment costs borne by the patients with the second fracture were significantly higher compared with single fracture patient, which is consistent with previous studies in USA and UK [ 16 18 ]. In this study, those with the second vertebral fracture bore more than twice of total medical costs and fracture treatment costs when comparing their point estimates with those with a single vertebral fracture.…”
Section: Discussionsupporting
confidence: 91%
“…In the base case analysis, we assumed the FLS is offered to all patients hospitalized with an index hip fracture. We assumed 75% of postfracture patients are female with an age distribution similar to that reported in several large studies of patients with an index fracture . We assumed 80% have low BMD—osteopenia or osteoporosis—based on data from a Canadian postfracture study…”
Section: Methodsmentioning
confidence: 99%
“…We assumed 75% of postfracture patients are female with an age distribution similar to that reported in several large studies of patients with an index fracture. (12)(13)(14) We assumed 80% have low BMDosteopenia or osteoporosis-based on data from a Canadian postfracture study. (15) The universal FLS strategy assumed that all patients receive care, whereas the targeted DXA strategy assumed FLS follow-up only for patients with low BMD.…”
Section: Characteristics Of Flsmentioning
confidence: 99%
“…Some investigators 8 have indicated that subsequent fractures are associated with an even greater increase in mortality rates and a significant higher cost. Pike et al, 9 in a recent study, further recommended that nonvertebral fracture patients are at substantial risk for subsequent nonvertebral fractures within 1 year, and patients who incur subsequent fractures are significantly more costly than those who do not during the year following an incident fracture. However, most studies mainly focus on the rates of subsequent fractures and the incurred cost.…”
mentioning
confidence: 95%